Математичні моделі динаміки виробництва в макроекономіці - Khoroshun, L. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A new principle of construction of the theory of production functions in macroeconomics is suggested. It is based on formulation of differential equations of dynamics of production in material form, which takes into account productivity, amortization and accumulation of real capital. The models of production with one and arbitrary number of freedom degree are considered for closed and open economics. Solutions of concrete problems are found. It illustrates the growth, recession, stable and cyclic character of production.